2006
DOI: 10.1111/j.1365-2567.2005.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus infection negatively impacts the CXCR4‐dependent migration of tonsillar B cells

Abstract: Summary The primary Epstein–Barr virus (EBV) infection occurs in the oropharynx, where the virus infects B cells and subsequently establishes latency in the memory B‐cell compartment. EBV has previously been shown to induce changes in the cell surface expression of several chemokine receptors in cell lines and the transfection of EBNA2 or LMP1 into a B‐cell‐lymphoma‐derived cell line decreased the expression of CXCR4. We show that in vitro EBV infection reduces the expression of CXCR4 on primary tonsil B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
(86 reference statements)
1
21
0
Order By: Relevance
“…by guest www.bloodjournal.org From Importantly, these data indicated that in CLL the mechanism of IL-4 is both receptor-and cell type-dependent. The IL-4-mediated downregulation of CXCR4 expression and function by CLL cells mirrors the effect of BCR stimulation on this receptor, 61,62 suggesting that these influences may be acting together to locate cells to extrafollicular sites 63 where enhanced IgM expression then increases antigen engagement and subsequent downstream signalling events.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From Importantly, these data indicated that in CLL the mechanism of IL-4 is both receptor-and cell type-dependent. The IL-4-mediated downregulation of CXCR4 expression and function by CLL cells mirrors the effect of BCR stimulation on this receptor, 61,62 suggesting that these influences may be acting together to locate cells to extrafollicular sites 63 where enhanced IgM expression then increases antigen engagement and subsequent downstream signalling events.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of CXCR4 expression appears to be a common feature of herpesvirus infection, as EBV, human herpesvirus 6, and human herpesvirus 7 have all been shown to downmodulate CXCR4 expression in infected B and T cells, respectively (36,53). In addition, EBV infection of primary tonsillar B cells results in downregulation of CXCR4 expression within 48 h, with a corresponding decrease in the ability of infected cells to respond to CXCL12 (7). Although the precise mechanism of EBNA-3B-mediated CXCR4 regulation remains to be defined, our preliminary studies suggest that EBNA-3B alone cannot repress CXCR4 expression in T-cell lines and that either the presence of other EBV genes or the context of an LCL background may be required for EBNA-3B-mediated modulation of CXCR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of EBV-infected CD19 ϩ cells in HL strongly suggests that the role of B lymphocytes in EBV spreading to oral epithelium is limited at best. Furthermore, it has been shown that EBV infection in B lymphocytes inhibits CXCR4 expression on the B-lymphocyte surface (9,27), leading to reduced migration of EBV-infected B lymphocytes toward stromal cell-derived factor 1 in vitro (9).…”
Section: Discussionmentioning
confidence: 99%